Rovibrational energy transfer in collisions of H2 with D2: a full-dimensional wave packet propagation study - Otto, Frank; Meyer, Hans-Dieter (Molecular physics, 2012)
We present full-dimensional quantum dynamics calculations for the process of rovibrational energy transfer in collisions between H2 and D2 molecules, specifically H2(ν = 1) + D2(ν = 0) → H2(ν = 0) + D2(ν = 1). Rotationally resolved state-to-state cross-sections are obtained for collision energies up to 0.5 eV. From these we calculate rotationally averaged thermal rate coefficients in the temperature range from 100 to 500 K, and compare them with available experimental data. For some transitions, we found it numerically advantageous to compute cross-sections of the reverse collision process and then use microscopic reversibility to obtain the originally sought cross-sections. We employ the Multi-Configuration Time-Dependent Hartree (MCTDH) method for propagating wave packets, and calculate the cross-sections from transition probabilities obtained by the correlation function formalism introduced by Tannor and Weeks. Computations are performed with a potential energy surface that is based on the six-dimensional surface from Boothroyd et al. but reduced in anisotropy, as suggested by Pogrebnya and Clary. The expression of the kinetic energy operator in terms of internal curvilinear coordinates allows us to treat the kinematics of the system exactly, without any decoupling approximations.
Gesehen am 24.04.2018